Antenatal visits and obstetric outcomes during nationwide COVID-19 lock down period in a tertiary hospital of Nepal - Gurung, Padma (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Maternity services were disrupted during nationwide COVID-19 lock down period. This study aimed to evaluate the impact of nationwide COVID-19 lock down on antenatal visits and obstetric outcomes in a tertiary hospital of Nepal.Method: A study was conducted at Patan hospital, Nepal with regard to antenatal visits and obstetric outcomes during COVID-19 lockdown period (24th March to 14th June 2020) and was compared to non COVID-19 period (24th March to 14th June 2019). A Chi-square test was used to determine the association between the outcome variables. The data was taken as statistically significant when the p-value was